IMPLEMENTASI METODE SELF DIRECTED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR SISWA DI SMA FATAHILLAH JAKARTA - Aisyi, Rifdah Rihadatul; Rahmanto, Muhammad Arifin (Jurnal Al-Fatih, 2025)
Education requires an innovative approach to improve students' thinking skills, one of which is through the Self-Directed Learning (SDL) method. The researcher's aim in conducting this research was to find out how the implementation of the self-directed learning method improves students' thinking skills at SMA Fatahillah Jakarta.This study uses a descriptive qualitative approach, with data collection through observation, interviews, and documentation involving grade XI students and Islamic Religious Education (PAI) teachers. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that students' critical, creative, and analytical thinking skills increased after the application of the SDL method. Students are given autonomy to choose teaching materials, set learning objectives, and choose the right learning resources, which fosters greater independence, responsibility, and motivation in learning. The application of the SDL method shows a positive impact on the development of students' high-level thinking skills at SMA Fatahillah Jakarta.